2019
DOI: 10.3164/jcbn.19-10
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of probiotic kimchi ameliorated IL-6-driven cancer cachexia

Abstract: Cancer cachexia is a syndrome accompanying weight loss, skeletal muscle atrophy, and loss of adipose tissue in patients with advanced cancer. Since interleukin 6 (IL 6) is one of core mediators causing cancer cachexia and kimchi can modulate IL 6 response, we hypothesized dietary intake of kimchi can ameliorate cancer cachexia. In this study, we studied preemptive administration of kimchi can ameliorate mouse colon carcinoma cells colon (C26) adenocarcinoma induced cancer cachexia and explored anti cachexic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…After checking their reference lists, we excluded reviews, book chapters, case reports, conference articles, and study protocols, which resulted in 35 research articles being left. These articles were screened fully to assess their eligibility, and eight articles were accepted for inclusion based on exposure, study population, and outcome measures [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. After reviewing the reference lists of the included articles and broadening the term “disease” to (“heart failure” OR COPD OR “renal failure” OR HIV), one additional study was included in the review [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…After checking their reference lists, we excluded reviews, book chapters, case reports, conference articles, and study protocols, which resulted in 35 research articles being left. These articles were screened fully to assess their eligibility, and eight articles were accepted for inclusion based on exposure, study population, and outcome measures [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. After reviewing the reference lists of the included articles and broadening the term “disease” to (“heart failure” OR COPD OR “renal failure” OR HIV), one additional study was included in the review [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cachexia is characterized by the activation of systemic inflammation, which is reflected by increased serum levels of C-reactive protein [ 57 ]; however, the catabolic drive during cancer cachexia can also be reflected by other cytokines, including IL-6 and TNFα. Increased levels of these cytokines were reported in association with sarcopenia and cachexia during conditions such as aging [ 58 , 59 ] and cancer [ 60 ], and nutritional interventions targeted at suppressing inflammation were shown to ameliorate cancer cachexia in experimental models [ 61 ]. The effects of protein and amino acid supplementation alone or associated with other interventions on serum concentrations of proinflammatory cytokines were investigated in three studies [ 36 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multimodal comprehensive treatment should be adopted to delay muscle atrophy caused by cachexia. related measures include activating the Pi3K/aKT/mTor signaling pathway (138,139), inhibiting the UPS (140,141), proinflammatory factors (142), signal transduction pathways (53,143) and transcription factors (144), and regulating the expression of certain organelles (145) and receptors (146) related to muscle atrophy caused by cancer cachexia.…”
Section: Treatment Of Muscle Atrophy Caused By Cancer Cachexiamentioning
confidence: 99%
“…A previous study identified that IL-6 and its receptor, as well as JAK2 and STAT3 were significantly attenuated with kimchi. Kimchi was discovered to be a potential option to ameliorate cancer cachexia through its ability to suppress il-6 and decrease muscle atrophy in a c26 mouse model (142). in addition, in an experimental model of c26-induced cancer cachexia, 20S, 21-epoxy-resibufogenin-3-acetate (erBa) markedly inhibited body weight loss.…”
Section: Treatment Of Muscle Atrophy Caused By Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation